(untitled) (Physical Education, Health and Social Sciences, 2025)
Individuals with disabilities (IWDs) in Pakistan constitute a large and marginalized demographic that is systematically left out of the formal financial system. This exclusion stifles economic development and perpetuates poverty. This research examines the financial inclusion of IWDs using a mixed-methods framework, gathering primary data from 60 participants in both Bahawalpur, Punjab, and Multan. A Financial Inclusion Index (FII), created through Principal Component Analysis (PCA), highlights a critical issue, revealing that only 16 of the respondents have access to financial services. The major obstacles identified include inadequate infrastructure, high costs, and a significant lack of trust in financial institutions. A One-way ANOVA analysis indicated that there are no meaningful differences in the levels of financial exclusion between semi-urban and urban areas, underscoring a nationwide accessibility crisis. These results call for urgent, comprehensive policy initiatives aimed at removing systemic barriers and enabling IWDs to engage as active contributors to the economy, rather than merely as recipients of support.